(untitled) (Research, Society and Development, 2022)
The entire food production chain must become more efficient and sustainable, so new technologies such as the use of growth-promoting bacteria associated with nitrogen fertilization tend to raise the production levels of corn and minimize the negative effects on the environment caused by synthetic nitrogen application.The objective of this work was to analyze the synergistic effect between the form of application of Azospirillum brasilense and nitrogen rates on corn productivity in sandy soil, located in the municipality of Nova Andradina-MS. The experimental design was randomized blocks in a 4 × 2 factorial scheme, encompassing four forms of application of A. brasilense (control; seed inoculation; inoculation in the sowing line at stage V2 and inoculation in canopy spraying at stage V4) and 2 doses of nitrogen (120 and 160 kg ha-1 of N, in coverage). The variables analyzed were root dry mass , root tissue nitrogen , stem diameter , first ear insertion height , plant height , number of grains per ear , 100-grain mass , leaf tissue nitrogen and corn grain yield. Nitrogen fertilization in corn, at the highest dose, promotes an increase in the concentrations of this element in root and leaf tissues. The ways of inoculation via foliar and in the sowing line are more efficient than the application via seed treatment, promoting gains in all parameters evaluated, except for the EIA. The application of A. brasilense potentiates the effect of N application on corn.